Economic Causes of Rural-to-Urban Migration in Karnali Province of Nepal - Ban, Padam; Gangal, Meenu (NPRC Journal of Multidisciplinary Research, 2024)
Migration is a natural phenomenon that is influenced by social, economic, political, geographic, and environmental factors. The main objective of this study is to identify the economic causes of rural-to-urban migration in Karnali province of Nepal. The study was conducted to test the research instrument so it took 40 respondents from the total 400 samples to test the readability and understandability of the survey questionnaire. The study was based on the quantitative data. It was a cross-sectional study. The simple random sampling technique was used to select the respondent. Crosstab, Chi-square test, and t-test were done to analyze the quantitative data. The result shows that the average mean value of each statement was a minimum of 3.7 to a maximum of 4.1 which is close to the ‘Agree’. Overall, the total mean score for economic causes of rural-to-urban migration is 3.9625, indicating that respondents perceive these factors as moderately to highly significant drivers of migration. This underscores the complex interplay of economic factors in shaping migration decisions, highlighting the importance of addressing economic disparities between rural and urban areas to mitigate migration pressures and promote balanced regional development. Further study can be done to identify the economic changes in migrant family in between before and after rural-to-urban migration.